METODE ACTIVE ISOLATED STRETCHING (AIS) DAN METODE HOLD RELAX STRETCHING (HRS) SAMA EFEKTIF DALAM MENINGKATKAN FLEKSIBILITAS OTOT HAMSTRING PADA MAHASISWA AKADEMI FISIOTERAPI WIDYA HUSADA SEMARANG YANG MENGALAMI HAMSTRING MUSCLE TIGHTNESS (HMTs) - alfajri, Akhmad; purnawati, susy; lesmana, indra (Sport and Fitness Journal; Volume 3, No.2, 2015)
Students with Hamstring Muscle Tightness (HMTs) will be at risk of Anterior Crusiatum Ligament (ACL), Low Back Pain (LBP) and also Plantar Faciitis. One of the efforts to reduce tightness and improve hamstring muscle flexibility is stretching. Active Isolated Stretching (AIS) and Hold Relax Stretching (HRS) are the methods of influential stretching to improve muscle flexibility. The goal of the research is to prove that AIS method is equally effective with the HRS method to improve hamstring muscle flexibility to the HMTs patients. The research method was true experimental with pre and post test group design. The research was conducted for 3 weeks and the samples are 23 students in range of 18-25 years old students of physical therapy in Physical Therapy Academy of Widya Husada Semarang which divided into 2 groups; AIS group (n= 12) and HRS group (n= 11). The research used Sit and Reach Test (SRT) as the measurement instrument. The result of the research was the average result of AIS group used SRT before treatment was 1.75 cm, SB= 4.309 and after treatment was 10. 58 cm, SB = 8. 005 within p= 0.000 (p 0.05). Those explain that the improvement of hamstring muscle flexibility to the two groups does not show any significant difference. Conclusion from this study was active isolated stretching method and hold relax stretching method are equally effective to improving muscle flexibility of hamstring muscle tightness students of physical therapy in Physical Therapy Academy of Widya Husada Semarang.
Keywords: Active Isolated Stretching, Hold Relax Stretching, Hamstring Muscle Tightness, Hamstring Flexibility And Sit And Reach Test.